Satisfaction with clinical practice environments among early-career health professionals in South Africa: Findings from the WiSDOM cohort study - Laetitia C Rispel; Prudence Ditlopo; Duane Blaauw (International Journal for Quality in Health Care, 2026)
Abstract Background The work or practice environments of health professionals play a central role in their retention in the healthcare system and their ability to provide quality patient care. The aim of the study was to examine and compare the satisfaction of early-career health professionals in the WiSDOM (Wits longitudinal Study to Determine the Operation of the labour Market among its health professional graduates) study with their clinical practice environments (CPEs) in South Africa, and the factors influencing their satisfaction. Methods WiSDOM, a prospective longitudinal cohort study, consists of eight health professions: clinical associates, dentists, doctors, nurses, occupational therapists, oral hygienists, pharmacists, and physiotherapists. Every year we collect information on the cohort’s involvement in direct patient care, their perceived workload, availability of medicines and equipment for patients in their care, and their satisfaction with the clinical practice environment (CPE). We used Stata®19 for analysis. We used panel linear regression to investigate factors associated with the cohort’s satisfaction with their clinical practice environments from 2018 to 2024, and logistic regression to evaluate the association between CPE and intention to leave in 2024. Results In 2024, the mean age of the cohort was 30.9 (± 2.0), the majority were female (74.4%) and working in urban areas (92.7%). In 2024, 59.7% of the overall cohort reported a heavy workload compared to 69.2% in 2018. Over the follow-up period, reported problems with the availability of medicines or equipment were worse in the public sector and in rural areas, compared to the private sector and urban areas respectively. The cohort’s satisfaction score with the CPE was 6.7 out of 10 in 2018 and 6.9 in 2024. The predictors of CPE were year of follow-up, health profession, employment sector, and geographic location. Nurses (β=-1.2; 95% CI -1.7, -0.7; p < 0.001), and pharmacists (β=-0.7; 95% CI -1.1, -0.4; p < 0.001) scored their CPE significantly lower compared to the other professional groups. Health professionals in the public sector (β=-1.1; 95% CI -1.3, -0.9; p < 0.001) and in rural areas (β=-0.6; 95% CI -0.9, -0.3; p < 0.001) were less satisfied with their CPE compared to those in the private sector and urban areas respectively. Dissatisfaction with the CPE was significantly associated with intention to leave the workplace and the profession. Conclusion The study findings underscore the need for positive clinical practice environments for early-career health professionals in South Africa both as a health workforce and patient safety imperative.